Electrolyte for lithium ion battery, lithium ion battery and preparation method thereof
Patent Information
- Application Number
- CN202110585792.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-27
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2041-05-27
AI Technical Summary
[0006]本发明的目的是为了解决现有锂离子电池在低温下锂离子传输阻抗大和在高温、过充条件下的电解液与正负极表面的副反应过多,从而导致锂离子电池的高温存储性能、低温放电性能、循环性能以及耐过充性能较差的问题,提供一种锂离子电池用电解液、锂离子电池及其制备方法,该锂离子电池具有更好的高温存储性能、低温放电性能、循环性能以及耐过充性能
[0015] Through the above technical solutions, this invention employs a specific battery composition system, namely a specific electrolyte, along with specific positive and negative electrode plates and separators, and uses a specific preparation process to enable the prepared lithium-ion battery to have superior high-temperature storage performance, low-temperature discharge performance, overcharge resistance, and cycle performance. In other words, the lithium-ion battery provided by this invention has superior comprehensive performance and broad application prospects.
Smart Images

Figure CN115411362B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to an electrolyte for lithium-ion batteries, a lithium-ion battery, and a method for preparing the same. Background Technology
[0002] With my country's increasing emphasis on environmental protection, the continuous maturation of science and technology, and the inherent advantages of lithium-ion batteries in terms of energy conservation and environmental protection, lithium-ion batteries are being used more and more widely in consumer electronics, electric vehicles, energy storage and other fields.
[0003] Operating temperature range is one of the important performance indicators of lithium-ion batteries. The maximum operating temperature range of lithium-ion batteries for conventional consumer products is typically -20 to 60°C. However, to adapt to large regional and seasonal temperature differences, the power supply for electric vehicles typically requires an operating temperature range of -30 to 70°C. Military and aerospace equipment requires even stronger adaptability, not only meeting the requirements for use in extremely cold and hot regions (-55 to 70°C), but also maintaining good low-temperature discharge performance, fast charging performance, and overcharge resistance after long-term high-temperature and low-temperature storage.
[0004] However, in currently used lithium-ion batteries, when the temperature is too low, the conductivity of the electrolyte decreases significantly, the SEI film impedance increases, and the transmission impedance of lithium ions in the electrodes also increases. At higher temperatures, the oxidation activity of the positive electrode material is high, further intensifying the reaction between the positive electrode and the electrode solution. This leads to the continuous deposition of electrolyte oxidation decomposition products on the positive electrode surface, resulting in a continuous increase in the battery's internal resistance and thickness. Simultaneously, transition metal oxides in the positive electrode active material are easily reduced and dissolved. Transition metal ions, after passing through the SEI film, are reduced to elemental metals on the negative electrode surface, leading to a continuous increase in negative electrode impedance and thus affecting the battery's low-temperature performance. Furthermore, during overcharging, the continuous reaction between the electrolyte and electrodes in currently used lithium-ion batteries causes the temperature to continue to rise, eventually leading to thermal runaway and safety issues.
[0005] It is evident that current lithium-ion batteries still struggle to operate at high performance for extended periods within such a wide temperature range. Therefore, there is an urgent need to develop a new type of lithium-ion battery with a wide temperature range and resistance to overcharging. Summary of the Invention
[0006] The purpose of this invention is to solve the problems of high lithium-ion transport impedance at low temperatures and excessive side reactions between the electrolyte and the positive and negative electrode surfaces under high temperature and overcharge conditions in existing lithium-ion batteries, which lead to poor high-temperature storage performance, low-temperature discharge performance, cycle performance and overcharge resistance. The invention provides an electrolyte for lithium-ion batteries, a lithium-ion battery and its preparation method, which have better high-temperature storage performance, low-temperature discharge performance, cycle performance and overcharge resistance.
[0007] To achieve the above objectives, a first aspect of the present invention provides an electrolyte for lithium-ion batteries, the electrolyte comprising an organic solvent, a lithium salt, and additives, wherein the additives comprise fluoroethylene carbonate, tris(trimethylsilane) phosphate, 3-fluoro-1,3-propanesulfonate lactone, and phenyl isothiocyanate compounds, wherein the phenyl isothiocyanate compounds have the structure shown in formula (1):
[0008]
[0009] R1, R2, R3, R4, and R5 are each independently selected from at least one of H, fluorine, fluoroalkyl, ethyl methoxy, ether, ethoxy, acetyl, vinyl, cyano, phenyl, cyclohexyl, isothiocyanate, and sulfonamide.
[0010] A second aspect of the present invention provides a lithium-ion battery comprising: a positive electrode, a negative electrode, a separator, an aluminum-plastic casing, and the electrolyte described in the first aspect of the present invention.
[0011] A third aspect of the present invention provides a method for preparing the lithium-ion battery described in the second aspect of the present invention, the method comprising:
[0012] (1) The positive electrode binder, positive electrode conductive agent, positive electrode active material and solvent-I are mixed to obtain a positive electrode slurry. Then the positive electrode slurry is uniformly coated on the positive electrode current collector to prepare a positive electrode sheet.
[0013] (2) Mix the negative electrode binder, negative electrode conductive agent, negative electrode active material and solvent-II to obtain a negative electrode slurry, and then uniformly coat the negative electrode material onto the negative electrode current collector to prepare a negative electrode sheet;
[0014] (3) The positive electrode, negative electrode and separator are made into a battery cell, the battery cell is placed in an aluminum-plastic packaging bag for sealing, and electrolyte is injected to obtain a battery semi-finished product. Then the battery semi-finished product is subjected to formation and aging in sequence to obtain a lithium-ion battery.
[0015] Through the above technical solutions, this invention employs a specific battery composition system, namely a specific electrolyte, along with specific positive and negative electrode plates and separators, and uses a specific preparation process to enable the prepared lithium-ion battery to have superior high-temperature storage performance, low-temperature discharge performance, overcharge resistance, and cycle performance. In other words, the lithium-ion battery provided by this invention has superior comprehensive performance and broad application prospects. Attached Figure Description
[0016] Figure 1 The discharge curve of the lithium-ion battery prepared in Example 1 of the present invention at -40°C and 1C rate is shown.
[0017] Figure 2 The lithium-ion battery prepared in Example 1 of this invention has a 1C / 6V overcharge voltage-temperature curve at 25°C.
[0018] Figure 3 The cycling curve of the lithium-ion battery prepared in Example 1 of this invention is shown at 25°C. Detailed Implementation
[0019] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0020] As previously stated, a first aspect of the present invention provides an electrolyte for lithium-ion batteries, the electrolyte comprising an organic solvent, a lithium salt, and additives, wherein the additives comprise fluoroethylene carbonate, tris(trimethylsilane) phosphate, 3-fluoro-1,3-propanesulfonate lactone, and phenyl isothiocyanate compounds, wherein the phenyl isothiocyanate compounds have the structure shown in formula (1):
[0021]
[0022] R1, R2, R3, R4, and R5 are each independently selected from at least one of H, fluorine, fluoroalkyl, ethyl methoxy, ether, ethoxy, acetyl, vinyl, cyano, phenyl, cyclohexyl, isothiocyanate, and sulfonamide. The electrolyte meeting the above-defined conditions has low viscosity at low temperatures, and the additives therein exhibit good film-forming properties, forming a thin, dense, and well-designed passivation film on the positive and negative electrode surfaces. It also effectively reduces the battery's internal resistance and prevents side reactions between the electrolyte and the positive and negative electrode surfaces. Using an electrolyte meeting the above-defined conditions in lithium-ion batteries can effectively improve the cycle performance, low-temperature discharge performance, high-temperature storage performance, and overcharge resistance of lithium-ion batteries.
[0023] According to a preferred embodiment of the present invention, R1, R2, R3, R4, and R5 are each independently selected from at least one of H, fluorine, acetyl, vinyl, cyano, isothiocyanate, and sulfonamide. This can further improve the high-temperature storage performance, low-temperature discharge performance, cycle performance, and overcharge resistance of lithium-ion batteries.
[0024] In this invention, phenyl isothiocyanate compounds with the structure shown in formula (1) have good deacidification and dehydration effects, can significantly improve the stability of electrolyte under high temperature and high voltage conditions, and can also be reduced at the negative electrode interface to form an SEI film. The reduction product complements and interacts with the passivation film formed by the reduction of fluoroethylene carbonate, etc., so that the SEI film formed after battery formation has more dense and stable characteristics, thereby improving the electrochemical performance of the battery. It can also complex with metal atoms on the positive electrode surface to form a CEI film, and complement and synergistically interact with the CEI film formed by tris(trimethylsilane) phosphate and 3-fluoro-1,3-propenesulfonate lactone, which can effectively suppress the oxidative decomposition of electrolyte and the dissolution of transition metals.
[0025] In particular, the inventors of this invention, through numerous experiments, discovered that a specific combination of tris(trimethylsilane) phosphate, 3-fluoro-1,3-propanesulfonate lactone, fluoroethylene carbonate, and phenyl isothiocyanate compounds having the structure shown in formula (1) can synergistically form a film on the surface of the positive electrode material, preventing the oxidation reaction between the electrolyte and the material surface and reducing the dissolution of transition metal elements at high temperatures. It can also form an SEI film on the surface of the negative electrode material, inhibiting the reduction reaction and decomposition of the solvent at the negative electrode interface, reducing the interfacial impedance, and increasing the oxidation decomposition potential of the electrolyte. This effectively improves the low-temperature discharge performance, high-temperature storage performance, cycle performance, and overcharge resistance of the wide-temperature-range overcharge-resistant battery.
[0026] In some embodiments of the present invention, preferably, the phenyl isothiocyanate compound having the structure shown in formula (1) is selected from 4-isothiocyanobenzenesulfonamide, 3,4-difluorophenyl isothiocyanate, pentafluorophenyl thioisocyanate, benzyl dithiocyanate, 3-fluorophenyl thioisocyanate, 4-fluorophenyl isothiocyanate, 2,5-difluorophenyl isothiocyanate, 2,6-difluorophenyl isothiocyanate, 1,3-difluoro-5-phenyl isothiocyanate, 1,2-difluoro-3-phenyl isothiocyanate, 2,4, At least one of the following: 6-trifluorophenyl isothiocyanate, 2,3,5,6-tetrafluorophenyl thioisocyanate, 1,2,4,5-tetrafluoro-3-phenyl thioisocyanate, 2-fluorophenyl thioisocyanate, 3-cyanophenyl thioisocyanate, 2-cyanophenyl isocyanate, 4-cyanophenyl thioisocyanate, 1,3-phenylene diisothiocyanate, 2,3,4-trifluorophenyl ester isothiocyanate, 1-vinyl-4-phenyl isothiocyanate, and 3-acetylphenyl isothiocyanate. All phenyl isothiocyanate compounds described in this invention are commercially available.
[0027] According to a preferred embodiment of the present invention, the phenyl isothiocyanate compound having the structure shown in formula (1) is selected from at least one of 3-fluorophenyl thioisocyanate, 4-fluorophenyl isothiocyanate, and 2-fluorophenyl thioisocyanate. In this preferred embodiment, the low-temperature discharge performance, high-temperature storage performance, cycle performance, and overcharge resistance of the lithium-ion battery can be further improved.
[0028] In some embodiments of the present invention, preferably, based on the total amount of the electrolyte, the content of the organic solvent is 70-88 wt%, the content of the lithium salt is 10-20 wt%, and the content of the additive is 0.5-15 wt%.
[0029] In some embodiments of the present invention, preferably, the mass ratio of fluoroethylene carbonate (FEC), tris(trimethylsilane) phosphate (TMSP), 3-fluoro-1,3-propanesulfonate lactone (PS), and phenyl isothiocyanate compounds is 0.5-5:0.3-1:0.5-3:1, more preferably 0.5-2:0.3-0.5:0.5-1.5:1. In this preferred case, the passivation films formed by the various additives on the positive and negative electrode surfaces complement and interact with each other, which is more conducive to the formation of dense, stable, and low-impedance SEI and CEI films.
[0030] The present invention allows for a wide range of choices for the organic solvent. Preferably, the organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethyl propionate, and propyl propionate; more preferably, it is selected from ethylene carbonate, propylene carbonate, ethyl propionate, and methyl ethyl carbonate. In this preferred embodiment, the viscosity of the electrolyte at low temperatures and its thermal stability at high temperatures can be further balanced.
[0031] According to a preferred embodiment of the present invention, the mass ratio of ethylene carbonate (EC), propylene carbonate (PC), ethyl propionate (EP), and ethyl methyl carbonate (EMC) is 1-5:1:1-5:5-20, more preferably 3-5:1:1-3:8-15, which is more conducive to reducing the viscosity of the electrolyte at low temperatures while taking into account its stability at high temperatures.
[0032] In some embodiments of the present invention, preferably, the concentration of the lithium salt in the electrolyte is 1-2 mol / L. In the present invention, the concentration of the lithium salt is calculated in terms of elemental lithium.
[0033] The present invention allows for a wide range of lithium salts. Preferably, the lithium salt is selected from at least one of LiPF6, LiFSI, LiPO2F2, LiBOB, LiODFB, and LiBF4. In this invention, when multiple lithium salts are used, the ratio between them is not particularly limited and can be a conventional choice in the art.
[0034] A second aspect of the present invention provides a lithium-ion battery comprising: a positive electrode, a negative electrode, a separator, an aluminum-plastic casing, and an electrolyte as described above. The lithium-ion battery obtained by using the above-described combination exhibits better high-temperature storage performance, low-temperature discharge performance, cycle performance, and overcharge resistance.
[0035] In some embodiments of the present invention, preferably, the positive electrode sheet includes a positive current collector and a positive electrode material, the positive electrode material includes a positive electrode active material, a positive electrode conductive agent and a positive electrode binder, and based on the total weight of the positive electrode material, the content of the positive electrode active material is 88-98 wt%, the content of the positive electrode conductive agent is 1-9 wt%, and the content of the positive electrode binder is 1-7 wt%.
[0036] In some embodiments of the present invention, preferably, the positive electrode active material is surface-coated lithium nickel cobalt manganese oxide, wherein the expression for lithium nickel cobalt manganese oxide is LiNi 1-x-y Co x Mn y O2, where 0 < x < 0.5, 0 < y < 0.5, and x + y < 1.
[0037] In some embodiments of the present invention, preferably, the coating material on the surface of the lithium nickel cobalt manganese oxide is selected from at least one of Al2O3, TiO2, and LiFePO4, more preferably TiO2. The present invention does not particularly limit the preparation process of the surface-coated lithium nickel cobalt manganese oxide, nor the amount of lithium nickel cobalt manganese oxide and the coating material used, as long as a uniformly coated lithium nickel cobalt manganese oxide can be obtained. Those skilled in the art can select materials as needed based on actual conditions.
[0038] The present invention has a wide range of choices for the positive electrode conductive agent. Preferably, the positive electrode conductive agent is selected from at least one of superconducting carbon black SP, graphite conductive agent KS-6, flake graphite, carbon nanotubes, carbon fibers and vapor-grown fibers.
[0039] The present invention has a wide range of choices for the positive electrode binder. Preferably, the positive electrode binder is polyvinylidene fluoride or styrene-butadiene rubber.
[0040] The present invention does not particularly limit the positive current collector, and can be any conventional choice in the art, such as including but not limited to using aluminum foil as the positive current collector.
[0041] In some embodiments of the present invention, preferably, the negative electrode sheet includes a negative electrode current collector and a negative electrode material, the negative electrode material includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder, and based on the total weight of the negative electrode material, the content of the negative electrode active material is 85-98 wt%, the content of the negative electrode conductive agent is 1-9 wt%, and the content of the negative electrode binder is 1-7 wt%.
[0042] The present invention has a wide range of choices for the negative electrode active material. Preferably, the negative electrode active material is selected from at least one of artificial graphite, natural graphite and mesophase carbon microspheres.
[0043] The present invention has a wide range of choices for the negative electrode binder. Preferably, the negative electrode binder is polyvinylidene fluoride or styrene-butadiene rubber.
[0044] The present invention has a wide range of choices for the negative electrode conductive agent. Preferably, the negative electrode conductive agent is selected from at least one of superconducting carbon black SP, graphite conductive agent KS-6, and carbon nanotubes.
[0045] The present invention does not particularly limit the negative electrode current collector, and can be any conventional choice in the art, such as including but not limited to using copper foil as the negative electrode current collector.
[0046] The present invention does not particularly limit the diaphragm, and can use conventional choices in the field, such as including but not limited to using double-sided coated ceramic diaphragms.
[0047] In particular, the inventors of this invention have discovered that a lithium-ion battery obtained by mixing an electrolyte containing an organic solvent, a lithium salt, and additives including fluoroethylene carbonate, tris(trimethylsilane) phosphate, 3-fluoro-1,3-propanesulfonate lactone, and phenyl isothiocyanate compounds having the structure shown in formula (1) in specific proportions, and combining it with specific positive electrodes, negative electrodes, and separators, exhibits better high-temperature storage performance, low-temperature discharge performance, cycle performance, and overcharge resistance. The inventors of this invention have further discovered that by using an organic solvent containing ethylene carbonate, propylene carbonate, ethyl propionate, and methyl ethyl carbonate in specific proportions, a lithium salt, and additives in preferred proportions as an electrolyte, and combining it with specific positive electrodes, negative electrodes, and separators, the high-temperature storage performance, low-temperature discharge performance, cycle performance, and overcharge resistance of the lithium-ion battery can be further improved.
[0048] A third aspect of the present invention provides a method for preparing a lithium-ion battery as described above, the method comprising:
[0049] (1) The positive electrode binder, positive electrode conductive agent, positive electrode active material and solvent-I are mixed to obtain a positive electrode slurry. Then the positive electrode slurry is uniformly coated on the positive electrode current collector to prepare a positive electrode sheet.
[0050] (2) Mix the negative electrode binder, negative electrode conductive agent, negative electrode active material and solvent-II to obtain a negative electrode slurry, and then uniformly coat the negative electrode material onto the negative electrode current collector to prepare a negative electrode sheet;
[0051] (3) The positive electrode, negative electrode and separator are made into a battery cell, the battery cell is placed in an aluminum-plastic packaging bag for sealing, and electrolyte is injected to obtain a battery semi-finished product. Then the battery semi-finished product is sequentially formed to obtain a lithium-ion battery.
[0052] According to the present invention, the properties such as the type and content of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder, the properties such as the type and content of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder, the type of the separator, and the type of the electrolyte are the same as those in the first aspect described above, and will not be repeated here.
[0053] The present invention does not have any particular limitation on the method of mixing the positive electrode binder, positive electrode conductive agent, positive electrode active material and solvent-I in step (1), as long as a uniform and stable positive electrode slurry can be obtained. Preferably, the positive electrode binder and solvent-I are first mixed to obtain an adhesive with a solid content of 2-10wt%, and then the positive electrode conductive agent, positive electrode active material and solvent-I are added to the adhesive in sequence to obtain the positive electrode slurry.
[0054] The present invention does not have any particular limitation on the way of mixing the negative electrode binder, negative electrode conductive agent, negative electrode active material and solvent-II in step (2), as long as a uniform and stable negative electrode slurry can be obtained. Preferably, the negative electrode binder and solvent-II are first mixed to obtain an adhesive with a solid content of 2-10 wt%, and then the negative electrode conductive agent, negative electrode active material and solvent-II are added to the adhesive in sequence to obtain the negative electrode slurry.
[0055] In some embodiments of the present invention, preferably, in step (1), the amount of solvent-I is such that the solid content of the obtained positive electrode slurry is 50-80 wt% and the viscosity is 5000-8000 mPa·s.
[0056] In some embodiments of the present invention, preferably, in step (2), the amount of solvent-II is such that the solid content of the obtained negative electrode slurry is 40-60 wt% and the viscosity is 1000-5000 mPa·s.
[0057] In this invention, by adjusting the solid content of the binder and the solid content and viscosity of the slurry, the powder materials can be fully mixed, thereby improving the uniformity of the materials in the slurry. In this invention, the mixing in steps (1) and (2) is carried out under stirring conditions. This invention does not impose any particular limitation on the stirring conditions, which can be determined by those skilled in the art based on the actual situation.
[0058] This invention does not particularly limit the type of solvent-I or solvent-II, and can use conventional choices in the art, such as including but not limited to at least one selected from N-methylpyrrolidone, dipropylene glycol dimethyl ether, and dimethylformamide. In this invention, solvent-I and solvent-II can be the same or different, and those skilled in the art can choose as needed based on actual circumstances.
[0059] In this invention, before uniformly coating the positive electrode slurry obtained in step (1) onto the positive electrode current collector or before uniformly coating the negative electrode slurry obtained in step (2) onto the negative electrode current collector, the method further includes passing the positive electrode slurry obtained in step (1) or the negative electrode slurry obtained in step (2) through a 150-mesh sieve.
[0060] In step (1) of this invention, the process of uniformly coating the positive electrode slurry onto the positive electrode current collector to prepare the positive electrode sheet specifically includes: uniformly coating the aforementioned prepared positive electrode slurry onto both sides of the positive electrode current collector and then drying, rolling, slitting, and welding the electrode tabs. The drying, rolling, slitting, and welding of the electrode tabs ensures that the moisture content of the prepared positive electrode sheet is ≤200ppm. Similarly, in step (2) of this invention, the process of uniformly coating the negative electrode slurry onto the negative electrode current collector to prepare the negative electrode sheet specifically includes: uniformly coating the aforementioned prepared negative electrode slurry onto both sides of the negative electrode current collector and then drying, rolling, slitting, and welding the electrode tabs. The drying, rolling, slitting, and welding of the electrode tabs ensure that the moisture content of the prepared negative electrode sheet is ≤200ppm.
[0061] In some embodiments of the present invention, preferably, the assembly process of step (3) specifically includes: making the positive electrode sheet, separator, and negative electrode sheet into a cell using a stacked structure or a wound structure; placing the cell into an aluminum-plastic packaging bag; leading out the positive and negative tabs respectively; heating the tab adhesive to fuse the PP layer of the aluminum-plastic bag with the tab adhesive; leaving one side of the soft-pack battery open for electrolyte injection; injecting the electrolyte into the cell; sealing the injection port; and completing the battery assembly.
[0062] In some embodiments of the present invention, preferably, in step (3), the formation conditions include: a formation temperature of 45-90°C and a formation pressure of 0.2-1 MPa.
[0063] In some embodiments of the present invention, preferably, in step (3), the formation process includes:
[0064] (a) Charge at a constant current of 0.01-0.05C for 10-60 minutes;
[0065] (b) Charge at a constant current of 0.1-0.2C for 10-60 minutes;
[0066] (c) Charge at a constant current of 0.5-1.0C until the cutoff voltage is 4.2V.
[0067] In particular, by employing a specific battery composition system, including selecting a specific electrolyte, combining specific positive electrode, negative electrode and separator, and using a specific formation process, the ester substances in the electrolyte fully react on the surfaces of the positive and negative electrodes to form a uniform and dense SEI film and CEI film. This enables the prepared lithium-ion battery to have more significant advantages over other combinations, namely, superior high-temperature storage performance, low-temperature discharge performance, cycle performance and overcharge resistance.
[0068] The present invention will be described in detail below through examples. In the following examples, unless otherwise specified, all raw materials used are commercially available.
[0069] Preparation Example
[0070] Preparation of electrolyte: Organic solvent, lithium salt and additives are mixed. The amount of each component is such that the content of organic solvent in the prepared electrolyte A1 is 83 wt%, the content of lithium salt is 14 wt%, the content of additives is 3 wt%, and the concentration of lithium salt is 1.2 mol / L. The specific formula is listed in Table 1.
[0071] The remaining preparation examples were carried out using the same process as Preparation Example 1, and the specific formulations are listed in Table 1.
[0072] Table 1
[0073]
[0074]
[0075] Example 1
[0076] (1) Preparation of the positive electrode:
[0077] The positive electrode binder was mixed with N-methylpyrrolidone and stirred at high speed for 1.5 h to obtain an adhesive with a solid content of 8 wt%. The positive electrode conductive agent was added to the adhesive and stirred at high speed for 60 min. Then the positive electrode active material was added and stirred at high speed for 3 h. Finally, N-methylpyrrolidone was added. The amount of N-methylpyrrolidone added was such that the solid content of the obtained positive electrode slurry was 65 wt% and the viscosity was 6000 mPa·s. The obtained positive electrode slurry was passed through a 150-mesh sieve and then evenly coated on both sides of the positive electrode aluminum foil current collector. The slurry was then dried, rolled, slit, and the tabs were welded to prepare a positive electrode sheet with a moisture content of ≤200 ppm.
[0078] (2) Preparation of negative electrode
[0079] The negative electrode binder was mixed with N-methylpyrrolidone and stirred at high speed for 1.5 hours to obtain an adhesive with a solid content of 8 wt%. The negative electrode conductive agent was added to the adhesive and stirred at high speed for 1 hour. Then the negative electrode active material was added and stirred at high speed for 4 hours. Finally, N-methylpyrrolidone was added. The amount of N-methylpyrrolidone added was such that the solid content of the obtained negative electrode slurry was 50 wt% and the viscosity was 4500 mPa·s. The obtained negative electrode slurry was passed through a 150-mesh sieve and then evenly coated on both sides of the negative electrode copper foil current collector. The slurry was then dried, rolled, slit, and the tabs were welded to prepare a negative electrode sheet with a moisture content of ≤200 ppm.
[0080] (3) Assembly of lithium-ion batteries
[0081] The above-mentioned positive electrode sheet, negative electrode sheet and double-sided coated ceramic separator are used to form a battery cell in a winding structure. The battery cell is placed in an aluminum-plastic packaging bag, and the positive and negative tabs are led out respectively. The tab adhesive is heated to fuse the PP layer of the aluminum-plastic bag with the tab adhesive. One side of the soft-pack battery is open to allow the electrolyte to be injected. Then, the electrolyte A1 is injected into the battery cell and the injection port is sealed to obtain a battery semi-finished product.
[0082] (4) Formation of lithium-ion batteries
[0083] Under certain formation conditions, the battery semi-finished product is formed to obtain lithium-ion battery B1.
[0084] The remaining embodiments and comparative examples were carried out using the same process as in Example 1. The formulations of the positive electrode material, negative electrode material, electrolyte, and the formation process and conditions are listed in Table 2.
[0085] Table 2
[0086]
[0087]
[0088] Table 2 (Continued from Table 1)
[0089]
[0090]
[0091] Table 2 (Continued)
[0092]
[0093] Table 2 (Continued from Table 3)
[0094]
[0095] Table 2 (Continued from Table 4)
[0096]
[0097]
[0098] Test Example 1
[0099] The lithium-ion battery B1 prepared in Example 1 was discharged at 0.2C at 25°C, and the discharge capacity was recorded as E. 初始 .
[0100] The lithium-ion battery B1 prepared in Example 1 was subjected to charge and discharge tests according to the following steps, and the different discharge capacities were recorded. Specifically:
[0101] (1-1) Perform a 0.5C discharge at -40℃ and record the discharge capacity E1;
[0102] (1-2) Discharge at 0.5C at 55℃ and record the discharge capacity E2;
[0103] (1-3) After storing at -55℃ for 24 hours, discharge at 0.5C and record the discharge capacity E3;
[0104] (1-4) Store at 70℃ for 48 hours;
[0105] (1-5) Perform 1C discharge at -40℃ and record the discharge capacity E4;
[0106] (1-6) First, charge at 1C for 1 hour, then discharge at 0.5C at 25℃, and record the discharge capacity E5;
[0107] (1-7) Under the conditions of 25℃ and 6V, 1C overcharge was performed. The overcharge phenomenon was that the battery did not catch fire or explode, and the highest surface temperature rise was 84.6℃.
[0108] Divide E1-E5 by E respectively 初始 F1-F5 were obtained, and the specific calculation results are listed in Table 3.
[0109] Table 3
[0110] B1 72.2 99.4 98.5 69.3 93.5 No fire, no explosion B2 70.2 99.1 98.2 66.3 92.3 No fire, no explosion B3 72.3 98.9 98.5 66.2 92.2 No fire, no explosion B4 69.9 99.2 98.1 66.9 92.5 No fire, no explosion B5 70.2 98.9 97.9 66.4 91.7 No fire, no explosion B6 70.2 97.9 98.6 65.8 90.7 No fire, no explosion B7 67.4 98.5 98.2 59.8 89.5 No fire, no explosion B8 65.3 99.2 98.3 58.4 89.3 No fire, no explosion B9 72.4 98.8 98.3 66.5 92.1 fire B10 68.5 98.1 98.1 65.8 91.2 fire B11 74.6 97.8 98.2 50.2 88.31 No fire, no explosion B12 74.5 97.8 98.2 60.8 89.77 fire B13 73.2 97.9 98.1 60.3 89.3 fire B14 71.2 98.9 98.2 65.2 90.7 fire DB1 64.5 97.8 97.9 52.2 88.5 fire DB2 70.8 98.6 98.5 55.6 90.8 fire DB3 71.4 98.4 97.6 54.4 89.3 fire DB4 72.6 98.3 97.8 55.3 88.2 fire DB5 70.2 98.8 98.2 55.3 89.3 No fire, no explosion
[0111] In addition, to further examine the high-temperature storage performance of the lithium-ion battery provided by the present invention, steps (1-4) in Test Example 1 were specifically performed as follows:
[0112] (A) Before storage, charge the lithium-ion battery to 4.2V at a constant current of 0.5C, with a cutoff current of less than 0.05C;
[0113] (B) Discharge the lithium-ion battery at a constant current of 0.5C(A) until the termination voltage is 2.5V;
[0114] (C) Charge the lithium-ion battery according to step (A);
[0115] (D) Let the lithium-ion battery stand at room temperature for 8 hours;
[0116] (E) Measure and record the initial internal resistance R1 and initial thickness d1 of the lithium-ion battery, and record the discharge capacity of step (B) as the initial capacity C1.
[0117] (F) Store the lithium-ion battery at 70°C for 48 hours;
[0118] (G) Let the lithium-ion battery sit at room temperature for 8 hours;
[0119] (H) Measure and record the internal resistance R2 and thickness d2 of the battery after storage;
[0120] (I) Discharge the lithium-ion battery according to step (B) and record the discharge capacity as the retention capacity C2;
[0121] (J) Charge the lithium-ion battery according to step (A), and then discharge it according to step (B). Record the discharge capacity as the recovery capacity C3.
[0122] Among them, the thickness expansion rate = (d2-d1) / d1, where d2 and d1 are in mm; the internal resistance growth rate = (R2-R1) / R1, where R2 and R1 are in mΩ; the retention percentage = C2 / C1; and the recovery percentage = C3 / C1, where C2, C3, and C1 are in Ah. The specific evaluation results are listed in Table 4.
[0123] In this invention, unless otherwise specified, room temperature refers to 25°C.
[0124] Table 4
[0125]
[0126]
[0127] As can be seen from the results in Tables 3 and 4, the lithium-ion battery prepared by this invention using a specific electrolyte, along with specific positive and negative electrodes and a separator, exhibits good temperature adaptability and overcharge resistance after a series of performance and overcharge tests. Furthermore, after being stored at 70°C for 48 hours, the lithium-ion battery provided by this invention maintains a high percentage of battery life and recovers its original capacity, with minimal changes in internal resistance and thickness, and virtually no gas buildup, indicating excellent high-temperature storage performance. Therefore, the lithium-ion battery provided by this invention possesses superior overall performance.
[0128] Figure 1The figure shows the discharge curve of the lithium-ion battery B1 prepared in Example 1 of this invention at -40°C and 1C rate. From... Figure 1 It can be seen that the lithium-ion battery provided by the present invention has good low-temperature discharge performance.
[0129] Figure 2 This shows the 1C / 6V overcharge voltage-temperature curve of the lithium-ion battery B1 prepared in Example 1 of the present invention at 25°C. Figure 2 It can be seen that the lithium-ion battery provided by the present invention has good overcharge resistance.
[0130] Test Example 2
[0131] The lithium-ion battery B1 prepared in Example 1 was charged to 4.2V at 25°C with constant current and constant voltage at 0.5C and cutoff current at 0.02C. Then it was discharged to 2.5V with constant current at 0.5C. This cycle was repeated 500 times to test the cycle performance of the lithium-ion battery.
[0132] Figure 3 This shows the cycling curve of the lithium-ion battery B1 prepared in Example 1 of the present invention at 25°C. From... Figure 3 It can be seen that the lithium-ion battery provided by the present invention has good cycle performance.
[0133] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. An electrolyte for lithium-ion batteries, characterized in that, The electrolyte comprises an organic solvent, a lithium salt, and additives. The additives include fluoroethylene carbonate, tris(trimethylsilane) phosphate, 3-fluoro-1,3-propanesulfonate lactone, and phenyl isothiocyanate compounds. The phenyl isothiocyanate compounds are selected from at least one of 3-fluorophenyl thioisocyanate, 4-fluorophenyl isothiocyanate, and 2-fluorophenyl thioisocyanate. The mass ratio of fluoroethylene carbonate, tris(trimethylsilane) phosphate, 3-fluoro-1,3-propanesulfonate lactone, and phenyl isothiocyanate compounds is 0.5-5:0.3-1:0.5-3:
1. The organic solvent is ethylene carbonate, propylene carbonate, ethyl propionate, and methyl ethyl carbonate, with a mass ratio of 3-5:1:1-3:8-15.
2. The electrolyte according to claim 1, wherein, Based on the total amount of the electrolyte, the content of the organic solvent is 70-88 wt%, the content of the lithium salt is 10-20 wt%, and the content of the additive is 0.5-15 wt%.
3. The electrolyte according to claim 1, wherein, The mass ratio of fluoroethylene carbonate, tris(trimethylsilane) phosphate, 3-fluoro-1,3-propanesulfonate lactone, and phenyl isothiocyanate compounds is 0.5-2:0.3-0.5:0.5-1.5:
1.
4. The electrolyte according to claim 1, wherein, In the electrolyte, the concentration of the lithium salt is 1-2 mol / L.
5. The electrolyte according to claim 1, wherein, The lithium salt is selected from at least one of LiPF6, LiFSI, LiPO2F2, LiBOB, LiODFB and LiBF4.
6. A lithium-ion battery, characterized in that, The lithium-ion battery comprises: a positive electrode, a negative electrode, a separator, an aluminum-plastic casing, and an electrolyte as described in any one of claims 1-5.
7. The lithium-ion battery according to claim 6, wherein, The positive electrode sheet includes a positive current collector and a positive electrode material. The positive electrode material includes a positive active material, a positive conductive agent, and a positive binder. Based on the total weight of the positive electrode material, the content of the positive active material is 88-98 wt%, the content of the positive conductive agent is 1-9 wt%, and the content of the positive binder is 1-7 wt%.
8. The lithium-ion battery according to claim 7, wherein, The positive electrode active material is a surface-coated lithium nickel cobalt manganese oxide, and the formula for lithium nickel cobalt manganese oxide is LiNi 1-x-y Co x Mn y O2, where 0 < x < 0.5, 0 < y < 0.5, and x + y < 1.
9. The lithium-ion battery according to claim 8, wherein, The coating material on the surface of the lithium nickel cobalt manganese oxide is selected from at least one of Al2O3, TiO2 and LiFePO4.
10. The lithium-ion battery according to claim 9, wherein, The coating material on the surface of the lithium nickel cobalt manganese oxide is TiO2.
11. The lithium-ion battery according to claim 7, wherein, The positive electrode conductive agent is selected from at least one of superconducting carbon black SP, graphite conductive agent KS-6, graphene, carbon nanotubes, carbon fibers, and vapor-grown fibers.
12. The lithium-ion battery according to claim 7, wherein, The positive electrode binder is polyvinylidene fluoride or styrene-butadiene rubber.
13. The lithium-ion battery according to claim 6, wherein, The negative electrode sheet includes a negative electrode current collector and a negative electrode material. The negative electrode material includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder. Based on the total weight of the negative electrode material, the content of the negative electrode active material is 85-98 wt%, the content of the negative electrode conductive agent is 1-9 wt%, and the content of the negative electrode binder is 1-7 wt%.
14. The lithium-ion battery according to claim 13, wherein, The negative electrode active material is selected from at least one of artificial graphite, natural graphite, and mesophase carbon microspheres.
15. The lithium-ion battery according to claim 13, wherein, The negative electrode binder is polyvinylidene fluoride or styrene-butadiene rubber.
16. The lithium-ion battery according to claim 13, wherein, The negative electrode conductive agent is selected from at least one of superconducting carbon black SP, graphite conductive agent KS-6, graphene, and carbon nanotubes.
17. A method for preparing a lithium-ion battery as described in any one of claims 6-16, characterized in that, The method includes: (1) The positive electrode binder, positive electrode conductive agent, positive electrode active material and solvent-I are mixed to obtain a positive electrode slurry, and then the positive electrode slurry is uniformly coated on the positive electrode current collector to prepare a positive electrode sheet; (2) The negative electrode binder, negative electrode conductive agent, negative electrode active material and solvent-II are mixed to obtain a negative electrode slurry, and then the negative electrode slurry is uniformly coated on the negative electrode current collector to prepare a negative electrode sheet; (3) The positive electrode, negative electrode and separator are made into a battery cell, the battery cell is placed in an aluminum-plastic packaging bag for sealing, and electrolyte is injected to obtain a battery semi-finished product. Then the battery semi-finished product is subjected to formation and aging in sequence to obtain a lithium-ion battery.
18. The method according to claim 17, wherein, In step (1), the amount of solvent-I used is such that the solid content of the obtained positive electrode slurry is 50-80wt% and the viscosity is 5000-8000mPa·s.
19. The method of claim 17, wherein, In step (2), the amount of solvent-II used is such that the solid content of the obtained negative electrode slurry is 40-60wt% and the viscosity is 1000-5000mPa·s.
20. The method of claim 17, wherein, Solvent-I or Solvent-II is selected from at least one of N-methylpyrrolidone, dipropylene glycol dimethyl ether, and γ-butyrolactone.
21. The method according to claim 17, wherein, In step (3), the formation conditions include: formation temperature of 45-90℃ and formation pressure of 0.2-1MPa.
22. The method according to claim 21, wherein, In step (3), the formation process includes: (a) Charge at a constant current of 0.01-0.05C for 10-60 minutes; (b) Charge at a constant current of 0.1-0.2C for 10-60 minutes; (c) Charge at a constant current of 0.5-1.0C until the cutoff voltage is 4.2V.
Citation Information
Patent Citations
Preparation method of 3-fluoro-1, 3-propanesultone
CN105037320A
Ternary cathode material lithium ion battery and electrolyte thereof
CN105591158A
Full-charge voltage formation method and device for flexible package lithium ion battery
CN110994037A
High-voltage low-impedance lithium ion battery electrolyte and lithium ion battery
CN112397785A
Low-temperature lithium iron phosphate cylindrical battery and manufacturing method thereof
CN112436150A